2019
DOI: 10.3390/en12091744
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Drive Chain Torsional Vibration for DFIG-Based Wind Turbine

Abstract: Due to the fast electric control of the doubly-fed induction generator (DFIG) when experiencing power grid disturbance or turbulent wind, the flexible drive chain of the wind turbine (WT) generates long-term torsional vibration, which shortens the service life of the drive chain. The torsional vibration causes fatigue damage of the gearbox and affects power generation. In this paper, a two-channel active damping control measure is proposed. The strategy forms a new WT electromagnetic torque reference value thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The concrete realization is divided into two steps: the first step is the extraction of the vibration signal of a specific frequency from the speed of the generator and filtering it with band-pass filter; the second step is to add the reverse torque for phase correction. The torque and damping control strategies can effectively suppress the drivetrain vibration caused by gear vibration [19,20].…”
Section: Suppression Strategy Of Gear Clearance Vibrationmentioning
confidence: 99%
“…The concrete realization is divided into two steps: the first step is the extraction of the vibration signal of a specific frequency from the speed of the generator and filtering it with band-pass filter; the second step is to add the reverse torque for phase correction. The torque and damping control strategies can effectively suppress the drivetrain vibration caused by gear vibration [19,20].…”
Section: Suppression Strategy Of Gear Clearance Vibrationmentioning
confidence: 99%
“…In Refs. [2,11,16,17,18], it is shown that a damping axillary term proportional to the difference between the rotational speeds of the turbine and generator can present superior performance over the methods based on feeding the generator speed through a BPF with and without considering the model uncertainty. However, these works are done based on the twomass drive-train model, and the blade flexibilities are ignored; furthermore, the WT operates in the speed or torque control modes.…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive researches on the control of DFIG in under normal and abnormal conditions of the power grid [4]. The direct power control method can reduce the current unbalance and torque ripple of stator and rotor [5,6]; The accurate control of the positive and negative sequence current of the rotor can be realized by the current predictive controller [7]; Proposes the control strategy based on reference current generator, which is used to control threephase inverters under balanced and unbalanced grid conditions, and the oscillation of reactive power has a good suppression effect [8]; A two-channel active damping control method is proposed to improve the electromagnetic torque of the drive chain and suppress the torsional vibration of the drive chain [9]; It will cause serious torque ripple that under the interaction of positive sequence, negative sequence and harmonic voltage and current [10,11]; The GSC can not only realize the voltage stability at the DC side, but also provide reactive power compensation and suppress harmonics to the grid [12]; The Chopper device is used to limit the overvoltage on the DC side, at the instant of the fault, the generator side converter blocks the pulse signal, and the rotor overcurrent charges the DC bus capacitor through the antiparallel diode of the machine side converter [13,14]; The control effect of the control strategy based on active demagnetization is limited by the capacity of the doubly-fed converter [15][16][17][18][19][20]; Introduce the rotor current transient feed forward term to minimize rotor transient current [21]; Control method of drive chain torsional vibration under power grid fault [22][23][24][25][26]; Control the mechanical torque to restrain the torsional vibration of drive chain [27,28]. Although the existing control methods have certain control effect on the unbalance of stator and rotor current in the power grid fault state, they rarely involve the active control of DFIG drive chain torsional vibration in the case of power grid asymmetric fault.…”
Section: Introductionmentioning
confidence: 99%